Effects of Solo Garlic Extract in Decreasing Malondialdehyde (MDA) Levels due to E-Cigarette Exposure - Aliefia Meta Duwairoh (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
The popularity of E-Cigarette has increased significantly over the last decade, and has potential to replace tobacco cigarettes. Aerosol which is produced by E-Cigarette, contains reactive carbonyl and free radicals, inducing oxidative stress and causing inflammation, proliferation, and cell damage. This oxidative stress can be seen through the Malondialdehyde (MDA) levels in the body, and reduced by antioxidant activity in Solo Garlic extract. The aim of this study is analyzing the differences of MDA levels in four treatment groups. 28 white rats were divided into four groups and three of them were exposured by E-Cigarette. This study showed that the highest MDA levels was found in the group which was exposured by E-Cigarette without solo garlic extract (7,179 nmol/ml). MDA levels can be reduced by antioxidant activity shown in the group which was exposured by E-Cigarette and solo garlic extract dose 0,05 gram/day (the smallest dose), amount 3,715 nmol/ml. The average of MDA levels in group which was given by the smallest dose of solo garlic extract, is lower than the control group. So, it can be concluded that using solo garlic extract less than 0,05 gram/day can restore MDA levels to a normal state (4,210 nmol/ml).